Noise Level of Factory Area Department IB PT Petrokimia Gresik Using Noise Mapping Method and Niosh - Surya Rizki Ramadhani; Dzakiyah Widyaningrum (Fakultas Teknik, 2023)
Noise is a problem in the industrial sector, this resulted in many cases of hearing loss due to noise in industrial areas. PT Petrokimia Gresik has implemented noise control and started implementing several elements/components of the Hearing Conservation Program (HCP)/Hearing Conservation Program (PKP) to control noise. However, the PKP special program has not been implemented systematically, only a few elements/components have been implemented. The research objective was to determine the mapping and noise level in the factory area in the IB department of PT Petrokimia Gresik using the Noise Mapping and Niosh methods. Based on the results of measurements in the field, there are 11 highest noise points which are above the noise level quality standard of Regulation Number Per.13/Men/X/2011 before control is carried out. The highest noise point is 106 dB at point 10. Based on noise level measurements, the length of exposure recommended by NIOSH varies, and depends on the measurement results obtained the longest exposure time allowed at point 10 is 34.2 minutes. This measurement point is closest to the noise source, so workers are required to use PPE in the form of ear plugs, ear muffs and safety hats. The PPE can reduce the amount of acoustic energy on the hearing mechanism of workers at PT Petrokimia Gresik.